Level 3 Diploma in Business Administration - Ashley, Vic; Ashley, Sheila; City and Guilds of London Institute (London : City & Guilds, 2015)
This series is written by experienced tutors in line with the level 2 specification. This volume covers business and adminstration.
Includes index.
Formerly CIP.
Keywords: Office management -- Examinations -- Study guides; Office management -- Textbooks; National Vocational Qualifications (Great Britain) -- Study guides